Legislating interprofessional collaboration: A policy analysis of health professions regulatory legislation in Ontario, Canada. Issue 4 (July 2015) - Regan, Sandra; Orchard, Carole; Khalili, Hossein; Brunton, Laura; Leslie, Kate
Abstract Changes to Ontario's health professions regulatory system were initiated through various legislative amendments. These amendments introduced a legislative obligation for health regulatory colleges to support interprofessional collaboration (IPC), collaborate where they share controlled acts, and incorporate IPC into their quality assurance programs. The purpose of this policy analysis was to identify activities, strategies, and collaborations taking place within health professions regulatory colleges pertaining to legislative changes related to IPC. A qualitative content analysis of (1) college documents pertaining to IPC (n = 355) and (2) interviews with representatives from 14 colleges. Three themes were identified: ideal versus reality; barriers to the ideal; and legislating IPC. Commitment to the ideal of IPC was evident in college documents and interviews. Colleges expressed concern about the lack of clarity regarding the intent of legislation. In addition, barriers stemming from long-standing issues in practice including scope of practice protection, conflicting legislation, and lack of knowledge about the roles of other health professionals impede IPC. Government legislation and health professional regulation have important roles in supporting IPC; however, broader collaboration may be required to achieve policy objectives.